1989
DOI: 10.2307/2409364
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis for Alternative Reproductive Tactics in the Pygmy Swordtail, Xiphophorus nigrensis

Abstract: Differences in adult male size and age at sexual maturity in the Río Coy (Mexico) population of Xiphophorus nigrensis (Pisces; Poeciliidae) are controlled by genetic variation at a Y-linked locus. Four genetic size-classes have been identified. The mating behavior of the males of the three largest size-classes consists exclusively of an elaborate courtship display, whereas that of the genetically small males ranges from display to a sneak-chase attempt at copulation. In the presence of large males, small males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 0 publications
6
113
1
Order By: Relevance
“…Glebe & Saunders (1986) noted that in Atlantic salmon, their observed frequencies of precocious male parr could be explained by a single gene model whereas sexual maturation in some Xiphophorus spp. has been determined to be controlled by a single locus (Kaliman & Bao, 1982;Zimmerer & Kallman, 1989). The present study showed that the sire The heritabilities were calculated from sire-male offspring regressions and sib-analysis (A NOVA) with progeny scored as ones (jacks) and zeros (non-mature males).…”
Section: Similar Results Have Been Reported For Coho Andmentioning
confidence: 99%
“…Glebe & Saunders (1986) noted that in Atlantic salmon, their observed frequencies of precocious male parr could be explained by a single gene model whereas sexual maturation in some Xiphophorus spp. has been determined to be controlled by a single locus (Kaliman & Bao, 1982;Zimmerer & Kallman, 1989). The present study showed that the sire The heritabilities were calculated from sire-male offspring regressions and sib-analysis (A NOVA) with progeny scored as ones (jacks) and zeros (non-mature males).…”
Section: Similar Results Have Been Reported For Coho Andmentioning
confidence: 99%
“…Astyanax mexicanus were collected from the Río Choy, Río Pánuco drainage, San Luis Potosí, Mexico, where they are sympatric with Xiphophorus nigrensis, the sister species of X. multilineatus (Rauchenberger et al 1990), which exhibits a body size polymorphism (Ryan and Causey 1989) and sword and body shape characteristics similar to X. multilineatus. Prior to the start of testing, male X. multilineatus were sorted by body size class (Zimmerer and Kallman 1989) into separate aquaria. For each tetra tested, we used a trio of X. multilineatus males from each phenotypic size class: small (!26 mm), intermediate (26-31 mm), and large (131 mm).…”
Section: Methodsmentioning
confidence: 99%
“…Small males reach sexual maturity earlier, are slender bodied, and lack conspicuous courtship displays. Large and intermediate males mature later, have robust bodies, and perform elaborate displays to potential mates (Ryan and Causey 1989;Zimmerer and Kallman 1989). Female northern swordtails X. multilineatus, X. nigrensis, and some populations of Xiphophorus pygmaeus all show preferences for large body size classes (Ryan and Wagner 1987;Ryan et al 1990).…”
mentioning
confidence: 99%
“…A captive breeding £ock of ru¡s has been maintained in Canada, established from eggs collected near Oulu, Finland, in 1985, 1989. We implanted 112 reeves from this £ock with testosterone immediately following breeding seasons in 1991^1995 (n 10, 33, 32, 21, 31 per season, respectively; 15 reeves were implanted in two di¡erent years).…”
Section: (A) Subjects and Pedigreesmentioning
confidence: 99%
“…However, in a small number of species, individuals do carry alternative alleles for reproductive strategies. In some, both sexes express polymorphic characteristics (seaweed £y, Coelopa frigida (Day & Gilburn 1997); whitethroated sparrows, Zonotrichia albicollis (Tuttle 1993); sideblotched lizards, Uta stansburiana (Sinervo & Lively 1996)), while others have sex-limited polymorphisms (marine isopod, Paracerceis sculpta (Shuster & Sassaman 1997); species of poeciliid ¢sh (Kallman 1983;Borowsky 1987;Ryan & Wagner 1987;Zimmerer & Kallman 1989;Erbelding-Denk et al 1994)). In the species listed above with polymorphisms in both sexes, autosomal models of inheritance have been proposed.…”
Section: Introductionmentioning
confidence: 99%